Indonesia’s Approach to International Treaties: Balancing National Interests and International Obligations - Atip Latipulhayat; Susi Dwi Harijanti (International Law Department, Faculty of Law Universitas Padjadjaran, 2022)
The relation and interaction between international and domestic law is one of the classic issues in international and it controversy remains in the realm of theory and practice. This is an issue of which many generations of both international and constitutional lawyers have wrestled, are wrestling and will continue to wrestle. For the Indonesian context, this issue is also still far from clear. The Indonesian Constitution of 1945 stipulates that the President of the Republic of Indonesia has the authority to conclude treaties with other countries. However, it does not clearly and specifically govern the status and position of international treaties under the Constitution. As a result, the Indonesian approach to international treaty is rather pragmatic, which is susceptible to some inconsistencies. It can be seen for instance in several decisions of the Indonesian Constitutional Court that clearly demonstrates the ambiguity towards international treaty. The Indonesian Parliament (DPR) argues that Indonesia should put emphasize to the national interests when Indonesia concluded international treaties. For a certain extent this approach is vulnerable to disregard international obligations in the name of national interests. There are some legislation for instance in the field of trade, which contains national interests clause that potentially will put Indonesia as the party that disregards its international obligations. This paper argues that national interests and international obligations are mutually inclusive, and not mutually exclusive element. To this end, international treaties should have a clear status and position under the Indonesian constitution to ensure that national interest and international obligation are working in harmony.